Setting research priorities for adolescent sexual and reproductive health in low- and middle-income countries - Michelle J Hindin; Charlotte Sigurdson Christiansen; B Jane Ferguson (The World Health Organization, 2013)
OBJECTIVE: To conduct an expert-led process for identifying research priorities in adolescent sexual and reproductive health in low- and middle-income countries. METHODS: The authors modified the priority-setting method of the Child Health and Nutrition Research Initiative (CHNRI) to obtain input from nearly 300 researchers, health programme managers and donors with wide-ranging backgrounds and experiences and from all geographic regions. In a three-Phase process, they asked these experts to: (i) rank outcome areas in order of importance; (ii) formulate research questions within each area, and (iii) rank the formulated questions. FINDINGS: Seven areas of adolescent sexual and reproductive health were identified as important: (i) maternal health; (ii) contraception; (iii) gender-based violence; (iv) treatment and care of patients with human immunodeficiency virus (HIV) infection; (v) abortion; (vi) integration of family planning and HIV-related services and (vii) sexually transmitted infections. Experts generated from 30 to 40 research questions in each area, and to prioritize these questions, they applied five criteria focused on: clarity, answerability, impact, implementation and relevance for equity. Rankings were based on overall mean scores derived by averaging the scores for individual criteria. Experts agreed strongly on the relative importance of the questions in each area. CONCLUSION: Research questions on the prevalence of conditions affecting adolescents are giving way to research questions on the scale-up of existing interventions and the development of new ones. CHNRI methods can be used by donors and health programme managers to prioritize research on adolescent sexual and reproductive health.